Peripapillary retinal nerve fiber layer and foveal thickness in hypermetropic anisometropic amblyopia - Yalcin E (Dove Medical Press, 2014)
Elvan Yalcin,1 Ozlem Balci21World Eye Hospital, Department of Pediatric Ophthalmology, 2Kolan Hospitalium Group, Istanbul, TurkeyPurpose: To evaluate whether there was a difference in peripapillary retinal nerve fiber layer (RNFL) and foveal thickness between amblyopic and normal individuals with optical coherence tomography.Materials and methods: Sixty patients, 30 patients with hypermetropic anisometropic amblyopia and 30 normal emmetropic subjects, were enrolled in this study. The eyes of the participants were divided into three groups: 30 eyes of 30 patients with amblyopia (A), 30 fellow eyes of the amblyopic patients (B), and 30 eyes of 30 normal subjects (C). Emmetropic normal subjects included cases with normal visual acuity and unremarkable ocular examinations. After routine ophthalmic examination, peripapillary retinal nerve fiber layer and foveal thickness measurements were measured by time-domain optical coherence tomography and compared among the three groups. Results: The difference in RNFL thickness between amblyopic eyes, fellow eyes of the amblyopic patients, and normal eyes of the emmetropic subjects was not clinically significant. However, the mean foveal thickness was significantly thicker in amblyopic eyes versus the fellow eyes and normal subjects' eyes.Conclusion: Our results suggest that amblyopia seems to have an effect on the foveal thickness, but not on the RNFL thickness.Keywords: RNFL thickness, foveal thickness, amplyopia